2020
DOI: 10.5267/j.msl.2019.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Gamification in learning process and its impact on entrepreneurial intention

Abstract: Gamification is an educational approach to motivate and influence students' behaviors in learning with the intention of achieving learning outcomes. The primary objective of the study is to examine students' intentions to become entrepreneurs as an impact of gamification model learning in Entrepreneurship or Business Plan courses in BINUS ONLINE Learning. Data collection was carried out for 400 students who took Entrepreneurship and Business Plan courses for 1 month using questionnaires. The data was then anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 31 publications
2
15
0
7
Order By: Relevance
“…In comparison, entrepreneurial schooling in the nation is considered to be inadequate in influencing students on the road to entrepreneurship and entrepreneurship . This is confirmed by the results of Aries et al (2020), who found that just 45% of all ISSN: 2456-7620 https://dx.doi.org/10.22161/ijels.62. 26 184…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…In comparison, entrepreneurial schooling in the nation is considered to be inadequate in influencing students on the road to entrepreneurship and entrepreneurship . This is confirmed by the results of Aries et al (2020), who found that just 45% of all ISSN: 2456-7620 https://dx.doi.org/10.22161/ijels.62. 26 184…”
Section: Introductionsupporting
confidence: 66%
“…In the meantime, if the goal of the EE is to create entrepreneurs, the optimal approach is to use market simulation or to play a role in facilitating experiments. Irrespective of the different methods used to meet a variety of goals, learning institutions have a key role to play in facilitating the transfer of EAs to students(Aries et al 2020). In the meantime, other (Prabhu et al 2020) had their own views on the EE.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, as Zhang and Price (2020) proposed that pedagogical alignment is key to entrepreneurship education, and gamification has been acknowledged for its potential in enhancing learners' performance and nurture their entrepreneurial competence with well-balanced alignment with other teaching modules (e.g. Aries et al 2020;Isabelle 2020;Kariv et al 2019).…”
Section: Gamification and Entrepreneurship Educationmentioning
confidence: 99%
“…For example, first-year students learned about using library resources through games to develop critical mindsets (O'Brien and Pitera, 2019). Games were used to teach sustainability (Gatti, Ulrich and Seele, 2019), entrepreneurship (Aries, et al, 2020) and, leadership (Sousa and Rocha, 2019). Nursing students developed decision-making skills through games (García-Viola, et al, 2019), and pharmacy and osteopathic students developed stronger interprofessional relationships by playing games (Boylan, et al, 2020).…”
Section: Serious Gamesmentioning
confidence: 99%